2015
DOI: 10.1080/10410236.2014.989384
|View full text |Cite
|
Sign up to set email alerts
|

Support Seeking or Familial Obligation: An Investigation of Motives for Disclosing Genetic Test Results

Abstract: Genetic test results reveal not only personal information about a person’s likelihood of certain medical conditions but also information about their genetic relatives (Annas, Glantz, & Roche, 1995). Given the familial nature of genetic information, one’s obligation to protect family members may be a motive for disclosing genetic test results, but this claim has not been methodically tested. Existing models of disclosure decision-making presume self-interested motives, such as seeking social support, instead of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 65 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Moreover, our data showed that the concept of family and feelings of responsibility shift when an individual starts her own family. The desire for social support from relatives, instead of feelings of obligation, may increase as a young adult begins a life with a significant other (Greenberg and Smith 2015;Whyte et al 2016).…”
Section: Family Responsibility and Care For Othersmentioning
confidence: 99%
“…Moreover, our data showed that the concept of family and feelings of responsibility shift when an individual starts her own family. The desire for social support from relatives, instead of feelings of obligation, may increase as a young adult begins a life with a significant other (Greenberg and Smith 2015;Whyte et al 2016).…”
Section: Family Responsibility and Care For Othersmentioning
confidence: 99%
“…Our findings suggest that co-management of health requires successful navigation of multiple processes related to information seeking, including assessment, ability, efficacy, and information sharing. Efficacy is an important component of the information sharing process (Greenberg & Smith, 2016;Greene, 2009). However, information theory focuses more on individuals and their assessment of the information and the receiver, with feelings of efficacy about sharing personal/private information stemming both from aspects of the relationship as well as of the individual (Greene, 2009; information management; see Venkatesh et al, 2003; authors, for efficacy as related to technology).…”
Section: Co-managementmentioning
confidence: 99%
“…Disclosure of positive genetic test results is important due to familial implications (Greenberg & Smith, 2016). Probands—the first individual in the family to get genetic test results—who test positive for a harmful BRCA genetic mutation disclose their positive genetic test results to their first-degree relatives at an average rate of 90% (Costalas et al, 2003; Finlay et al, 2008; McGivern et al, 2004).…”
Section: Communication About Brca-related Cancer Risks and Family Plamentioning
confidence: 99%